Diverse Presentation of Retained Intrauterine Bones: Case and Literature Review - Yadav, Reena; Parveen, Shama; Jaiswal, Nishtha; Dhar, Swati (International Journal of Human and Health Sciences (IJHHS), 2021)
Abortions are considered a safe procedure. Nevertheless, it may have many unwanted complications. The complications are mostly short term and resolve on their own. Some complications take months or even years to manifest. They may hamper the quality of life of the woman, depending upon the symptoms and signs . One such complication is retained intrauterine fetal bones. It is an uncommon complication but can produce a spectrum of complications which may be minor like discharge per vaginum or major such as secondary infertility or abnormal uterine bleeding. We are presenting two cases each having the same post abortal complication of retained intrauterine fetal bones but with different clinical presentations. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 510-513